"Too shocked to search" the COVID-19 shutdowns' impact on the search for apprenticeships - Daniel Goller; Stefan C. Wolter (Swiss Journal of Economics and Statistics, 2021)
Even though the recession in Switzerland triggered by COVID-19 ultimately remained without consequences for the apprenticeship market, significantly fewer apprenticeship contracts had been signed in the months of the first shutdown in 2020 than in the same months of the previous year. Using daily search queries on the national administrative platform for apprenticeship vacancies from February 2020 until April 2021 as a proxy for the supply of potential apprentices, we find a temporal pattern that coincides perfectly with the development of signed apprenticeship contracts. Furthermore, the analyses show that the initially very strong relationship between the intensity of the politically imposed restrictions to fight the COVID-19 pandemic and the daily search queries diminished over time, leading to a search intensity in March 2021 that was back at pre-pandemic level.
Keywords: I20; J22; 330; COVID-19; Switzerland; Stringency Index; Apprenticeship; Vacancies